Authority or Competence of the State Administrative Court (PTUN) on Dispute Subjects in Indonesia - Sri Wahyuni Ermawati (JUSTICES: Journal of Law, 2024)
The authority or competence possessed by PTUN includes absolute competence and relative competence. The absolute competence of PTUN can be seen from the point of view of the object, material or subject matter of the dispute, namely relating to the issuance of policies from TUN bodies or officials in the form of written decrees or decisions. Meanwhile, relative competence is related to the location or jurisdiction of the court itself, as well as the parties to the dispute. Based on Article 1 point (8) of Law 51/2009, the subjects of disputes in the PTUN are individuals or civil legal entities and TUN bodies or officials. Meanwhile, the object of the dispute is the TUN Decision, which is a written determination issued by a TUN body or official based on applicable laws and regulations, which is concrete, individual and final, which can give rise to legal consequences for a person or civil legal entity. This is stated in Article 1 number (9) of Law 51/2009.